PENGARUH HUKUM BISNIS TERHADAP STABILITAS EKONOMI NASIONAL MOH IQRA NEGARA - NEGARA, MOH IQRA; Lie, Gunardi (UM.Tapanuli Selatan, 2025)
Business law plays a crucial role in building an economic system that is stable, fair, and sustainable. Clear regulations supported by consistent enforcement help create legal certainty for entrepreneurs, investors, and society as a whole. This study explores how business law influences national economic stability by looking at legal protection, dispute resolution, and investment regulation. The findings suggest that a well-functioning legal framework can boost economic growth by attracting more investment, creating jobs, and ensuring a fairer distribution of resources. On the other hand, weak law enforcement can lead to uncertainty, monopolistic practices, and corruption, all of which slow down economic progress. When laws are poorly enforced, they can lead to uncertainty, unfair monopolies, and even corruption, all of which hold back economic growth. That’s why having business laws that are applied firmly, fairly, and transparently is so important — they provide a solid foundation for maintaining national economic stability and boosting the country s competitiveness inan ever-changing global environment.